Olfactory Ensheathing Cells Protect Cortical Neuron Cultures Exposed to Hypoxia - Pellitteri, Rosalia; Russo, Antonella; Stanzani, Stefania; Zaccheo, Damiano (CNS & Neurological Disorders - Drug Targets, 2015)
A peculiar population of glial cells, Olfactory Ensheathing Cells (OECs), are able to support the continuous neuronal turn-over and sheathe olfactory axons. In vitro, they stimulate axonal growth, as produce several neurotrophic factors (GFs); in vivo they promote remyelination of damaged axons. In this in vitro study, OEC effects on survival of cortical neurons exposed to hypoxia were examined. Rat co-cultures of OECs and cortical neurons were placed both in normal and hypoxic conditions; subsequently cells were analyzed by immunocytochemistry. Furthermore, some neuronal cultures were grown with Glial cell Derived Neurotrophic Factor (GDNF) or basic Fibroblast Growth Factor (bFGF) to tentatively rescue cells from oxygen deprivation. Some cortical neurons grown in both conditions were considered as control cells. Some neuronal cultures were feed with conditioned medium from OECs. We show that both in co-cultures and with GFs-treatment there was an increase of the number of neurons in comparison with control cultures. Moreover, these neurons formed a rich axonal outgrowth. OEC-conditioned media did not affect the cell survival. In hypoxic cultures the neuron number was very low both in controls and in GFs-treated neurons, while in co-cultures and in OEC-conditioned media cultures an increased neuronal survival was observed. These data suggest that OECs promote the survival of neurons in vitro exposed to hypoxia exerting a protective influence. Since some experiments in vivo have shown that injury is often characterized by secondary insults, ischemia or hypoxia, our results suggest that OECs might be considered a possible approach for restoration in injuries.
Keywords: neuroprotective effect